Aerofoil theory for swallow tail wings of small aspect ratio - Robinson, A. (College of Aeronautics, Cranfield, 1950)
A method is developed for the calculation of the aerodynamic forces acting on a ‘swallow tail’ wing of small aspect ratio. Lift, induced drag, and aerodynamic centre position of simple swallow tail wings (Fig. 1 (b)) are computed as an application. For a given incidence, lift and induced drag are, within the limits of the theory, proportional to aspect ratio and independent of speed. The chordwise life distribution rises linearly from zero at the apex, drops rapidly in the region of the root chord trailing edge, and then decreases gently to zero.